1992
DOI: 10.1002/jez.1402640407
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of the adrenocortical response to stress in birds of the Sonoran desert

Abstract: Many avian species of the North American Sonoran desert, e.g., the black-throated sparrow, Amphispiza bilineata, cactus wren, Campylorhynchus brunneicapillus, and curve-billed thrasher, Toxostoma curvirostre, can potentially breed from March/April to August. It is possible that, at least in summer, intense heat and aridity may have inhibitory effects on breeding by precipitating a stress response. Stress typically results in a rise in secretion of adrenocorticosteroid hormones that then inhibit reproduction by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
409
3
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 656 publications
(419 citation statements)
references
References 20 publications
6
409
3
1
Order By: Relevance
“…Indeed, Adams et al [1] felt that the reduced stress response they observed in grey-faced petrels was due to habituation. However, while we cannot rule out habituation as an explanation for our results, we believe that our findings (and possibly those of Adams et al [1] may reflect developmental differences between the handled and unhandled birds because the blood sampling technique used to induce the adrenocortical response [66] differs markedly from the daily handling procedures to which the birds were exposed. That is, during blood sampling the birds were immobilized, serially bled from a wing vein, and held in cloth bags in between sampling events, none of which the birds experienced during the daily handling protocol.…”
Section: Habituationcontrasting
confidence: 52%
See 3 more Smart Citations
“…Indeed, Adams et al [1] felt that the reduced stress response they observed in grey-faced petrels was due to habituation. However, while we cannot rule out habituation as an explanation for our results, we believe that our findings (and possibly those of Adams et al [1] may reflect developmental differences between the handled and unhandled birds because the blood sampling technique used to induce the adrenocortical response [66] differs markedly from the daily handling procedures to which the birds were exposed. That is, during blood sampling the birds were immobilized, serially bled from a wing vein, and held in cloth bags in between sampling events, none of which the birds experienced during the daily handling protocol.…”
Section: Habituationcontrasting
confidence: 52%
“…A few days prior to fledging, when the kestrels were 26 days old, we performed a standard capture and handling stress series [65]. From each next box we collected baseline blood samples from one randomly selected nestling within 3 min of opening the box.…”
Section: Capture and Handling Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Sufficient plasma for T assays was obtained from 40 males, totaling 388 blood samples during 12 months. The T concentration was measured by the method of radioimmunoassay, using an antibody for T (reference #RDI-TRK2T2) from Research Diagnostics Inc. (Flanders, USA) and following the procedure described by Wingfield et al (1992). The cross-reactivities provided by the supplier are 16% for 5-α-dehydrotestosterone, 1% for androstendiol, 0.4% for androstendione, b0.1% for androsterone, b0.1% dehydroepiandrosterone, b0.1% for progesterone, b0.01% for estradiol/estriol, and 0.01% for cortisol/ pregnenolone.…”
Section: Hormone Assaysmentioning
confidence: 99%